DISIPLIN KERJA DAN SEMANGAT KERJA DAMPAKNYA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PADA PT. NIKOMAS GEMILANG SERANG BANTEN - Muhammad Saleh (LP2M Universitas Bina Bangsa, 2022)
Every company that was founded has the hope that someday in the future will experience rapid development in the business environment of the company and wants the creation of high productivity in the field of work. This study aims to determine the effect of discipline and enthusiasm for work productivity employees at PT. Nikomas Gemilang Serang Banten. The research method used is quantitative methods with a correlational approach. The population of this study was 40 of employees and the determination of the number of samples of saturated sample techniques in which the entire population was sampled, as many as 40 samples. The results of the discipline study did not have an effect on work productivity in obtaining the results of tcount <ttable or -0.182 <1.68595 and the significance value was smaller than 0.05 ie 0.000 with a significance level <0.05. Then it can be concluded that Ho was accepted and Ha was rejected. The influence of morale on work productivity is obtained tcount> ttable or 4.028> 1.68595 and the significance value is smaller than 0.05 which is 0.000 with a significance level <0.05. Then it can be concluded that Ha was accepted and Ho was rejected. The conclusion of this study which states that the variables of discipline and work morale affect the work productivity of employees at PT. Nikomas Gemilang. Means an increase in discipline and morale will indirectly affect the performance of an employee